(untitled) (Scientia Agropecuaria, 2024)
Phytopathogenic nematodes are a threat for agriculture, they cause plant diseases and economic losses worldwide. Currently, the pursuit of compounds of biological origin for nematode biocontrol has become a priority as an environmentally friendly alternative. Microorganisms-derived compounds have several strategies to reduce the populations of infectious juvenile nematodes. Although microorganisms and their metabolites are the focus of literature reports reviews on nematicidal control, interactions between fungi, bacteria, and nematodes, as well as the compounds that are generated in such interactions, are not highlighted. The aim of this review was to discuss the latest advances on chemical compounds secreted by microorganisms and their interaction mechanisms for biological control of phytopathogenic nematodes. Results were organized based on: i) mode of action, ii) infection process, iii) nematicide compounds, iv) interactions and field applications, and v) current challenges. The scope of this review contributes to a better comprehension of the versatility of bacterial and fungal compounds for their use in the development of management plans for nematode control.